Sosialisasi Literasi Keuangan Digital Melalui Webinar untuk Meningkatkan Pemahaman Mahasiswa Terhadap Pinjaman Online - Kuntadi, Yahya Agung; Satyawati, Endang; Asmarawati, Sandra Galuh (Universitas Dinamika, 2025)
The development of financial technology (fintech), especially online loans (pinjol), has provided easy access to financial services, but also poses risks, especially for students who are vulnerable to the trap of illegal pinjol. This study aims to analyze the effectiveness of digital financial literacy socialization activities through the